Raudatul Athfal (RA) Job Satisfaction in Colomadu Karanganyar District - Bety Ratnaningsih; Istiatin; Sarsono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of Job Characteristics on Job Satisfaction, Burden on Job Satisfaction, Environment on Job Satisfaction, Compensation on Job Satisfaction of Teacher Raudatul Athfal (RA) in Colomadu District, Karanganyar. The research site is in each Raudatul Athfal (RA) location in Colomadu Karanganyar District. The research was conducted for 6 (six) months with a span of time between January to June 2024. Starting from the initial step is observation, sample determination, to the creation of data results from the research conducted, as well as determining the results and concluding the results of the research conducted. This study uses a quantitative method with the distribution of questionnaires using a Likert scale with multiple linear regression analysis with the help of SPSS 24 software. This study was conducted on 66 samples who were RA teachers in Colomadu Karanganyar District. The results showed that the characteristics of work and environment had a positive and significant effect on job satisfaction, while burden and compensation did not have a positive and significant effect on job satisfaction. Keywords: Job satisfaction, Characteristics, Burden, Environment, Compensation